2013
DOI: 10.18060/2514
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Leaders Project: Connecting University Resources to Community-Based Organizations Supporting Refugee Resettlement

Abstract: In recent decades, populations seeking refuge have underscored the limitations of what have been standard approaches to resettlement. Shrinking resources, post-9/11 increase in security measures, and the diverse needs and assets of new arriving populations have exacerbated existing weaknesses in U.S. social service delivery systems and challenged neighborhoods inexperienced in these areas with complex issues of integration (Kerwin, 2011). In response to these issues, the University of Utah, the Utah State Refu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Industry collaboration and cross‐sector partnerships have shown positive results in the US (Hunter and Mileski 2013) and in Jordan (Libal and Harding 2011) by enhancing a support organization's capability to act as an intermediary between refugees and employers. Recently, refugee‐run organizations have also been identified as potential partners in comprehending and capitalizing on refugees’ qualifications and experience and reaching out to the wider refugee community (Easton‐Calabria 2016).…”
Section: Organizational‐level Factorsmentioning
confidence: 99%
“…Industry collaboration and cross‐sector partnerships have shown positive results in the US (Hunter and Mileski 2013) and in Jordan (Libal and Harding 2011) by enhancing a support organization's capability to act as an intermediary between refugees and employers. Recently, refugee‐run organizations have also been identified as potential partners in comprehending and capitalizing on refugees’ qualifications and experience and reaching out to the wider refugee community (Easton‐Calabria 2016).…”
Section: Organizational‐level Factorsmentioning
confidence: 99%
“…In addition to other resettlement and integration support, newcomer support organisations help refugees to find employment through job counselling, language and training programmes and employment and volunteering initiatives. Studies also shine light on the benefits of crosssector partnerships and industry collaborations, boosting the capability of refugee support organizations to act as an intermediary between refugees and employers (Hunter and Mileski, 2013). Such stakeholder partnerships across private, government and nongovernmental organisations seek to tackle the challenges of workforce integration, highlighted by firms like Chobani and Ikea training and hiring refugees in receiving countries (e.g.…”
Section: Gtm At the Organisational Level-meso Conceptualisationsmentioning
confidence: 99%
“…The support of local volunteers is also highlighted by Cara, including host families providing accommodation and social support. Studies shine light on the benefits of cross-sector partnerships and industry collaborations, boosting the capability of refugee support organisations to act as an intermediary between refugees and employers (Hunter and Mileski, 2013). In this case, Cara galvanises support and resources from across the sector, and beyond, to secure their work as a charitable organisation and their related programmes which are essential in addressing the needs of academics in exile.…”
Section: Accessing and Developing Refugee Talentmentioning
confidence: 99%
“…Bryan et al (2014) reported that research findings provided evidence for a funding proposal for a health clinic and solidified the commitment to health in the community, including support from a private benefactor. Hunter and Mileski (2013) described the development of mentoring processes between communitybased organisations and the City Council, a new women's committee in the Office for Refugee services, and the introduction of a formal academic program at the college.…”
Section: Impact Reach and Significancementioning
confidence: 99%
“…The quality of the evaluations varied depending on the purpose and style of evaluation. Three authors (Bryan et al, 2014;Littlechild et al, 2015;Stanley et al, 2015) reported on formal, purposeful evaluations, while three (Home et al, 2015;Hunter and Mileski, 2013;Ringstad et al, 2012) reported reflective, introspective evaluations of the process. When a formal evaluation was used many aspects of the evaluation process were evident.…”
Section: Quality Appraisal Of Studies Reporting On Evaluationsmentioning
confidence: 99%